Efek Multiplier Wakaf Uang Dan Pengaruhnya Terhadap Program Pengentasan Kemiskinan - Al Arif, M. Nur Rianto (UIN Sunan Kalijaga, 2012)
One of the Islamic fiscal instrument is waqf that have been played a significant role in economics. Cash waqf is a new instrument in the field of waqf and Islamic economics as a facility for the purpose of worship and to achieve social welfare. The development of the waqf field through cash waqf, management which is flexible and offers many choices. Cash waqf have the multiplier effect in economic, through this effect cash waqf can be used as instrument to poverty alleviation program through community empowerment program.